Increased expression of CD20 and CD45 and diminished expression of CD19 are features of follicular lymphoma - Liu Q; Weaver LS; Liewehr D; Venzon D; Stetler-Stevenson M; Yuan CM (Dove Medical Press, 2013)
Qingyan Liu,1 Linda S Weaver,1 David Liewehr,2 David Venzon,2 Maryalice Stetler-Stevenson,1 Constance M Yuan11Flow Cytometry Unit, Laboratory of Pathology, 2Biostatistics and Data Management Section, National Cancer Institute, National Institutes of Health, Bethesda, MD, USAAbstract: Follicular lymphoma (FL) is a relatively common, well-characterized lymphoma with recognizable morphologic and immunophenotypic features. Nevertheless, close examination of its immunophenotypic profile by mean fluorescent intensity (MFI) and potential relationship between antigens, as well as histologic grade, has not been extensively assessed by flow cytometry immunophenotyping (FC). We examined the immunophenotypic profile, including heavy and light chain analysis, of 41 nodal FL cases with FC analysis and tissue diagnosis. Additionally, MFI of CD45, CD19, CD20, CD22, and CD10 were examined. The relationship between the antigen expression on FL cells and normal B cells in the same sample, and any association with each other or with histologic grade, were analyzed statistically. We observed brighter CD45 and CD20 expression in FL than normal B cells (P < 0.0001); dimmer CD19 in FL than normal B cells (P = 0.03); brighter CD20 in grade 2 than grade 1 histology (P = 0.0023). No correlation was observed between CD10 MFI and other antigens. Increased expression of CD20, CD45, and dim expression of CD19 are features of nodal FL. FC assessment of MFI detects subtle changes in antigen expression not entirely apparent by visual examination of dot plots or immunohistochemistry. MFI is a means of uncovering subtle but unique immunophenotypic features in both well-known, and less well-defined neoplastic hematolymphoid entities.Keywords: lymphoma, lymphoproliferative disorder, flow cytometry, mean fluorescent intensity, immunophenotyping, immunoglobulin heavy chain